R KESALAHAN PENGGUNAAN PEDOMAN EJAAN BAHASA INDONESIA PADA SKRIPSI MAHASISWA MATEMATIKA ANGKATAN 2019 BIDANG MATEMATIKA KOMBINATORIKA UNIVERSITAS ANDALAS - Daramenra, Romie (UNIVERSITAS PGRI YOGYAKARTA, 2023)
This research aims to describe forms of errors in the use of Indonesian spelling guidelines (PUEBI) which include errors in word fragmentation, use of punctuation marks, and writing mathematical symbols. This research is a qualitative descriptive research with a content analysis approach and a case study type of research. The results of this research are the analysis and identification of types of errors in the use of PUEBI and standard Indonesian grammar in the thesis field of mathematics combinatorics for mathematics students class of 2019 at Andalas University.